Novel algorithm for sinusoidal interference cancellation - Nosan, A.; Punchalard, R.; Wardkein, P.; Koseeyaporn, J. (My University, 2011)
A simple and efficient method for canceling sinusoidal interference is presented in this paper. The interference of known frequency is modeled as a sum of unknown amplitude and zeros phase sine and cosine components. The amplitude of those components are sequentially estimated interms of Wiener-Hopf solutions using cumulative average system. Additionally, in order to avoid any look-up tables for generating the sine and cosine signals, the coupled-digital oscillator is employed instead. It has been demonstrated that the proposed method can efficiently and rapidly cancel sinusoidal interference as compared with the previous method. © 2011 IEEE.
Keywords: coupled-oscillator; interference cancellation; Wiener-Hopf solution